2009
DOI: 10.1002/da.20624
|View full text |Cite
|
Sign up to set email alerts
|

Severity of anxiety and work-related outcomes of patients with anxiety disorders

Abstract: Level of work performance was generally associated with severity of anxiety. Of the instruments tested, the WLQ and the WPAI questionnaire demonstrated acceptable validity and internal reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 27 publications
3
90
0
1
Order By: Relevance
“…In contrast, the degree of work productivity impairment in the past 7 days, as measured by the WPAI, reported in BED respondents (absenteeism: 9.59%±19.17%; presenteeism: 30.0%±31.64%) tended to be smaller in magnitude than in individuals with moderate to severe depressive symptoms (absenteeism + presenteeism: 46.9%–51.3%)18 or with moderate to severe anxiety (absenteeism: 16%±20%; presenteeism: 45%±30%) 19…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, the degree of work productivity impairment in the past 7 days, as measured by the WPAI, reported in BED respondents (absenteeism: 9.59%±19.17%; presenteeism: 30.0%±31.64%) tended to be smaller in magnitude than in individuals with moderate to severe depressive symptoms (absenteeism + presenteeism: 46.9%–51.3%)18 or with moderate to severe anxiety (absenteeism: 16%±20%; presenteeism: 45%±30%) 19…”
Section: Discussionmentioning
confidence: 81%
“…For example, depressed workers reported greater experienced difficulties in time management, mental, interpersonal and output job demands [2,3]. Other research showed that poor health and multiple health problems were associated with low work performance [4].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is characterized by recurrent, unprovoked and unpredictable panic attacks, followed by concern of subsequent attacks, resulting in a strong social and functional inhibition. 3,4 Estimates from family and twin studies ascribe a genetic contribution of approximately 40% to the disease etiology of the disorder. [5][6][7][8] However, the mechanism underlying PD is still unknown and presumably involves numerous susceptibility genes with major and/or minor effects.…”
Section: Introductionmentioning
confidence: 99%